Restoration of phosphate transport by the phosphate-binding protein in spheroplasts of Escherichia coli. - Gerdes, R G (1977)
Reconstitution of phosphate transport in Escherichia coli was demonstrated. Conversion of E. coli K10 cells to spheroplasts decreased phosphate transport to about 2%. Addition of purified phosphate-binding protein at physiological levels to these spheroplasts caused a mean 14-fold increase in phosphate transport rate. Crude shock fluid fractions were also stimulatory but not if the shock fluid was obtained from mutants lacking phosphate-binding protein. The effect of the binding protein was abolished by its specific antibody. The phosphate was shown to have entered the cell, where it became esterified. Reconstitution was not possible with cold-shocked or osmotically shocked cells.